Determination of biochemical indicators when modeling HIPEC with cisplatin on rats - Pykhtieieva, E. D.; Tretyakov, A. M.; Gozhenko, A. I.; Pykhtieieva, E. G. (Journal of Education, Health and Sport, 2019)
HIPEC (Hyperthermic intraperitoneal chemotherapy; hyperthermic intraoperative intraperitoneally chemoperfusion) is a method of treating primary and secondary peritoneal tumors. Perfusion of the peritoneal cavity with solutions with cytotoxic agents at a temperature above the physiological norm (41-43 ° C) occurs when HIPEC. The conducted biochemical studies suggest that with HIPEC, elevated temperature is an important factor and leads to potentiation of the toxic effect of cisplatin. Despite the higher accumulation of platinum in the kidneys during cold solution perfusion, the resulting change in biochemical parameters is higher with the simultaneous action of elevated temperature and cisplatin.